PENGUKURAN MATURITY LEVEL CONTROL OBJECTIVE KE-8 DOMAIN DELIVERY AND SUPPORT : MANAGE SERVICE DESK AND INCIDENTS (Studi Kasus pada SIMAK di STMIK Mardira Indonesia) - Dheni Apriantsani Budiman (STMIK Mardira Indonesia, Bandung, 2018)
In order for Higher Education to get maximum benefits and benefits, it is necessary to have a well structured Information Technology management. The implementation of information technology at STMIK Mardira Indonesia is one of which is the Academic and Student Management Information System that has been running from 2002 and continues to develop along with the increase in data managed and its functions.Maturity Level shows the condition of the success of IT governance and recommendations that can improve IT governance in accordance with the main objectives of STMIK Mardira Indonesia. The COBIT 4.1 domain used is the DS domain (delivery & support) and the focus of control objectives is DS8-Manage Service Desk and Incidents, the results of the DS8 maturity level calculation, as-is maturity level 2. While the want (to-be) that is level 3 By looking at maturity level 2, it is necessary to recommend to take corrective action in accordance with the Maturity Attribute that has been set through the COBIT 4.1 FrameworkKeywords: Information Systems, Information Technology Governance, COBIT 4.1 DOI:10.5281/zenodo.3232913